Integrating Expressive Writing into Nursing Care for Schizophrenia Patients with Hallucinations: A Case Report - Bela Puspita Sari; Erti Ikhtiarini Dewi (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: Hallucinations represent a common sensory perception disorder in schizophrenia patients, affecting 70-80% of cases. Expressive writing therapy serves as a potential non-pharmacological intervention to reduce hallucination symptoms through emotional catharsis and distraction mechanisms. To analyze the effectiveness of expressive writing therapy in reducing hallucination symptoms in schizophrenia patients. Methods: A qualitative case study was conducted on a 23-year-old female patient with hebephrenic schizophrenia diagnosis at Dr. Radjiman Wediodiningrat Mental Hospital Lawang. The intervention was performed for 3 days combining expressive writing therapy 20 minutes/day and hallucination management implementation strategies. Data were collected through observation, interviews, and document analysis. Results: A significant reduction in hallucination symptoms was observed, decreasing from 5 symptoms to 3 symptoms post-intervention. The patient demonstrated improved ability to control hallucinations through rejecting techniques (100%), regular medication adherence (100%), and beginning social interaction capability. Emotional expression through writing showed progression from traumatic experiences toward positive hopes. Conclusion: Expressive writing therapy is effective as an adjuvant intervention in reducing hallucination symptoms and enhancing emotional expression in schizophrenia patients.